The Rate of Surplus Value in Puerto Rico - Wolff, Edward N. (Journal of Political Economy, 1975)
Puerto Rico's transformation from a preindustrial to an industralized economy in the period 1948-63 provides an opportunity to measure the impact of technological change on several basic parameters in a Marxian economic framework. The rate of surplus value (estimated using the Morishima-Seton transformation) remains relatively stable at 0.97 in 1948 and 0.93 in 1963, while the organic composition falls from 2.75 to 2.09. The stability in the rate of surplus value results from a 63 percent average fall in labor values counterbalanced by a 143 percent rise in labor's consumption. The rate of surplus value, when adjusted for trade flows, jumps to 1.31 in 1948 and 1.18 in 1963, due to Puerto Rico's large balance-of-trade deficit and the relative import intensity of labor's consumption.